TGT (Teams Games Tournament) Cooperative Learning Model in Kanji Courses to Improve Japanese Vocabulary Mastery - Alo Karyati; Paramita Winny Hapsari (Journal of Japanese Language Education and Linguistics, 2024)
Mastering kanji is a challenge for anyone studying the Japanese language. Due to its intricate nature, many students perceive kanji as an intimidating topic. The students' struggle with comprehending kanji directly impacts their ability to understand words written in kanji. Consequently, kids lack comprehension of the reading (dokkai) due to the abundance of kanji words inside it. To tackle this issue, it is necessary to develop a pedagogical paradigm that promotes cooperation among students, enabling them to effectively overcome challenges related to kanji. The TGT (Teams Games Tournament) model is a collaborative learning model that incorporates groups consisting of 3 to 5 individuals. The research aims to investigate the extent of your proficiency in mastering the JLPT N4 kanji vocabulary prior to utilizing the TGT (Teams Game Tournament) model. What is your proficiency in learning the JLPT N4 kanji vocabulary like after utilizing the TGT (Teams Games Tournament) approach? What is the students' response to studying kanji using the TGT (Teams Games Tournament) model? The research methodology employed is a combination of qualitative and quantitative methods. The research focused on a population of 3rd semester students, consisting of a total of 22 individuals. The data gathering methods employed in this study involved the utilization of questionnaires and interviews conducted using Google Form. Meanwhile, the data analysis technique employs descriptive statistics to assess pretest and posttest scores. The findings of this study demonstrated a notable improvement in students' proficiency of JLPT N4 kanji vocabulary after the implementation of the TGT (Teams Game Tournament) cooperative learning paradigm.